Стан наукової розробленості питань затримання особи без ухвали слідчого судді - Маник, О. В.; Manyk , O. V. (Наше право. - 2018. - № 3. - С. 250-256, 2018)
З’ясовано стан наукової розробленості як одного із напрямів дослідження питань затримання особи без ухвали слідчого судді. Наголошено, що інститут затримання особи без ухвали слідчого судді упродовж усього часу викликає зацікавленість як з боку теоретиків, так і практиків, адже він водночас є заходом забезпечення кримінального провадження, дозволяє припинити (попередити) кримінальну протиправну діяльність та зібрати доказову інформацію, пов’язаний із обмеженням прав і свобод людини в рамках кримінального провадження тощо. Встановлено, що проблематика затримання уповноваженою службовою особою без ухвали слідчого судді піднімається та вирішується не тільки в наукових працях, які присвячені тільки цій вузькій проблематиці, а і в наукових напрацювань, присвячених більш широкому предмету дослідження, а саме – застосуванню заходів забезпечення кримінального провадження та інституту затримання в кримінальному процесі.

In this article, it has been emphasized that clarifying the state of scientific development of issues of detaining a person without a decision of an investigating judge is one of the prerequisites for the development of the specified institute in criminal procedural law. It has been emphasized that the institution of detaining a person without a decision of an investigating judge has always been of interest to both theoreticians and practitioners, because it is at the same time a measure to ensure criminal proceedings, allows to stop (prevent) criminal illegal activity and collect evidentiary information related to restriction of human rights and freedoms within the framework of criminal proceedings, etc. It has been found that such multifacetedness of the specified legal institution undoubtedly leads to the emergence of a number of difficulties both in its regulation by the norms of criminal procedural legislation and bringing it into line with international and European legal standards, and in its application. It has been established that when detaining a person in criminal proceedings, in particular without a decision of the investigating judge, a large number of violations are allowed by authorized officials who encroach on the rights, freedoms and legitimate interests of the participants in criminal proceedings, which, in turn, is unacceptable in the legal and welfare state. It has been found that, despite the development of the outlined scientific problems, many questions still arouse interest and lively discussion both on the part of scientists and practical workers, which, in turn, only emphasizes the importance of further research into the theoretical and legal foundations of the institution of detention in criminal proceedings, the grounds and procedural order of detaining a person, in particular, without the decision of an investigating judge, ensuring the protection of rights, freedoms and legitimate interests during the detention of a person. It has been established that the issue of detention by an authorized official without a decision of the investigating judge is raised and resolved not only in scientific works devoted only to this narrow issue, but also in scientific works devoted to a broader subject of research, namely, the application of measures to ensure criminal proceedings and the institute detention in criminal proceedings.

Выяснено состояние научной разработанности как одного из направлений исследования вопросов задержания лица без постановления следственного судьи. Отмечено, что институт задержания лица без постановления следственного судьи на протяжении всего времени вызывает заинтересованность как со стороны теоретиков, так и практиков, ведь он одновременно является мерой обеспечение уголовного производства, позволяющее прекратить (предупредить) уголовную противоправную деятельность и собрать доказательную информацию, связанную с ограничением прав и свобод человека в рамках уголовного производства. Установлено, что проблематика задержания уполномоченным должностным лицом без постановления следственного судьи поднимается и решается не только в научных работах, посвященных этой узкой проблематике, но и в научных наработках, посвященных более широкому предмету исследования, а именно – применению мер обеспечения уголовного производства и института задержания в уголовном процессе.
The state of scientific development of issues of detaining a person without a decision of an investigating judge
Keywords: наукова розробленість; scientific development; научная разработанность; наукові дослідження; scientific research; научные исследования; кримінальне провадження; criminal proceedings; уголовное производство; затримання особи без ухвали слідчого судді; detention of a person without a decision of the investigating judge; задержание лица без постановления следственного судьи